2019
DOI: 10.1109/jas.2019.1911486
|View full text |Cite
|
Sign up to set email alerts
|

Verification of hypertorus communication grids by infinite petri nets and process algebra

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Ever since its inception in 1962, Petri Nets have been used for modeling of discrete event systems. Petri net is still an active research area; research papers on newer applications (e.g., [41], [42]), and the analysis (e.g., [43]- [45]) continue to appear. However, its huge size, and its state-space, and the slow execution (and simulation) prevents its use for modern large real-life applications, e.g., Industry 4.0.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since its inception in 1962, Petri Nets have been used for modeling of discrete event systems. Petri net is still an active research area; research papers on newer applications (e.g., [41], [42]), and the analysis (e.g., [43]- [45]) continue to appear. However, its huge size, and its state-space, and the slow execution (and simulation) prevents its use for modern large real-life applications, e.g., Industry 4.0.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the encapsulation operator, which is denoted by ∂ H , will force all internal atomic actions into either communication if there is a send action at one end of a channel and a read action at the other one, or otherwise they go deadlock, thus obtaining a sequence of events due to the interaction of all entities being part of the system [21]. At a later stage, the abstraction operator, which is described by τ I will mask both internal actions and internal communications, hence allowing only the external atomic actions, thus unveiling the external behavior of the model [22]. At that point, the external behavior of the real system may also be worked out, and if both external behaviors share the same string of actions and the same branching structure, it may be concluded that they are both rooted branching bisimilar, which is a sufficient condition to have a model verified [23].…”
Section: Algebraic Modeling With Acpmentioning
confidence: 99%
“…An interesting application of a Petri net is presented by Zaitsev et al (2019). The paper proposes a model of a hypertorus communication grid in which a particular cell can be the representation of a bioplast cell or packet switching device.…”
Section: Introductionmentioning
confidence: 99%